The effect of resistance training on physical function is associated with changes in serum albumin redox state in middle-aged and older Japanese adults: a Quasi-experimental study - Shibasaki, Takuya; Nakamura, Hirohiko; Kurosaka, Yuka; Sawada, Shuji; Miyaji, Kazuhiro; Machida, Shuichi (Frontiers in Physiology, 2025)
BackgroundResistance training is important for improving physical function in middle-aged and older adults. The fraction of mercaptoalbumin in total serum albumin, represented as f(HMA), is an indicator of physical function and protein nutritional status in humans. However, it is unclear whether the effects of resistance training on physical function are associated with changes in f(HMA). This study was aimed at examining the relationship between f(HMA) and the effects of resistance training in healthy middle-aged and older Japanese adults.MethodsThe study included 43 healthy community dwelling middle-aged and elderly individuals (10 males and 33 females, aged 67.3 ± 8.0 years). They were engaged in a low-load, body-weight-based resistance training program using an elastic band twice a week for 12 weeks under supervision. Anthropometric data, 6-meter gait speed, blood biochemistry, and dietary macronutrient intake were collected before and after the training intervention. The relationships between serum nutritional parameters and gait speed or their rate of change were examined using multivariate linear regression analysis.ResultsBefore intervention, f(HMA) showed a significant positive correlation with the usual (β = 0.326, P = 0.045) and maximum (β = 0.331, P = 0.036) gait speeds. The changing rate of maximal gait speed showed a significant positive correlation with the rate of increase in f(HMA) (β = 0.456, P = 0.004).ConclusionSerum f(HMA) increased with improvements in physical function through resistance training in middle-aged and older adults.